An Expedient Protocol to the Synthesis of Benzo(b)furans by Palladium Induced Heterocyclization of Corresponding 2-Allylphenols Containing Electron Rich and Electron Capturing Substituents in the Arene Ring. (30th October 2012) - Rao, Kiran; Tyagi, Ruchi; Kaur, Navjeet; Kishore, D.
Abstract : A facile and rapid accessibility to the libraries containing several mono, and disubstituted benzo(b)furan derivatives substituted with a variety of electron rich and electron capturing groups on 2, 4, 5, 6, and 7 positions of its nucleus has been explored using the PdCl2 (CH3 CN)2 catalyzed heterocyclization of the corresponding 2-allylphenols to afford 2(a –m) in good yield and high purity.